EPCO-35. THE ZINC FINGER IN THE CEREBELLUM (ZIC1/4) LOCUS IS A CONTEXT DEPENDENT DRIVER GENE IN MEDULLOBLASTOMA. (14th November 2022) - Lee, John; Tao, Ran; You, Zhen; Huang, Frank; Northcott, Paul; Taylor, Michael
Abstract: Medulloblastoma (MB) is a malignant paediatric brain tumor comprised of 4 molecularly and clinically distinct subgroups: WNT, SHH, Group 3 and Group 4. Previous studies have reported recurrent, mutually exclusive epigenetic modifier mutations converging in these subgroups, as well as aberrant H3K27me3 depositions within these tumors. While these observations hint at aberrant epigenetic mechanisms driving MB pathobiology, detailed understanding of MB chromatin landscape remains elusive to date. As such, chromatin landscape of MB was defined by conducting H3K27Ac ChIP-Seq in 102 primary MB tumors and H3K27me3 ChIP-Seq in 63 overlapping tumors. Chromatin landscape of Medulloblastoma was subgroup specific and H3K27me3 modification recurrently repressed ZIC1 in Group 3 and 4 MB, a driver gene that is also recurrently mutated within Group 4 and SHH MB. Validation cohort comprised of 251 MB samples with matching RNA-Seq and WGS data demonstrated that the ZIC1 - ZIC4 locus ( ZIC1/4 ) undergoes recurrent epigenetic repression of single alleles in 25% of Group 3, 50% of Group 4 but rarely in other subgroups. Strikingly, ZIC1 mutations in the Group 4 tumors always occurred in the context of repression of the wildtype allele, revealing a recurrent convergence of genetic and epigenetic mechanisms targeting both copies of ZIC1 . Overexpression of ZIC1 and ZIC4 together, or ZIC1 alone to a lesser extent, lead to reduced proliferation of Group 3 MB cells in vitro and in vivo . Intriguingly, while Group 4 ZIC1 mutations exhibited loss of function phenotypes, SHH ZIC1 mutations exhibited gain of function phenotypes. Overexpression of ZIC1 in Granule Progenitor Cells (GPC), which give rise to SHH MB, resulted in increased proliferation of cells in contrast to Group 3 MB cells. Taken together, we demonstrate that multiple epigenetic and genetic mechanisms converge to govern context dependent driver roles for ZIC1 and ZIC4 underlying MB pathobiology.